Nutritional behavior of cyclists during a 24-hour team relay race: a field study report - Bescos, R,; Rodriguez, F. A.; Iglesias, X.; Knechtle, B.; Benitez, A.; Marina, M.; Padulles, J. M.; Torrado, P.; Vazquez, J.; Rosemann, T. (Journal of the International Society of Sports Nutrition, 2012)
Information about behavior of energy intake in ultra-endurance cyclists during a 24-hour team relay race is scarce. The nutritional strategy during such an event is an important factor which athletes should plan carefully before the race. The purpose of this study was to examine and compare the nutritional intake of ultra-endurance cyclists during a 24-hour team relay race with the current nutritional guidelines for endurance events. Additionally, we analyzed the relationship among the nutritional and performance variables. Methods Using a observational design, nutritional intake of eight males (mean +/- SD: 36.7 +/- 4.7 years; 71.6 +/- 4.9 kg; 174.6 +/- 7.3 cm; BMI 23.5 +/- 0.5 kg/m2) participating in a 24-hour team relay cycling race was assessed. All food and fluid intake by athletes were weighed and recorded. Additionally, distance and speed performed by each rider were also recorded. Furthermore, before to the race, all subjects carried out an incremental exercise test to determine two heart rate-VO2 regression equations which were used to estimate the energy expenditure. Results The mean ingestion of macronutrients during the event was 943 +/- 245 g (13.1 +/- 4.0 g/kg) of carbohydrates, 174 +/- 146 g (2.4 +/- 1.9 g/kg) of proteins and 107 +/- 56 g (1.5 +/- 0.7 g/kg) of lipids, respectively. This amount of nutrients reported an average nutrient intake of 22.8 +/- 8.9 MJ which were significantly lower compared with energy expenditure 42.9 +/- 6.8 MJ (P = 0.012). Average fluid consumption corresponded to 10497 +/- 2654 mL. Mean caffeine ingestion was 142 +/- 76 mg. Additionally, there was no relationship between the main nutritional variables (i.e. energy intake, carbohydrates, proteins, fluids and caffeine ingestion) and the main performance variables (i.e. distance and speed). Conclusions: A 24-hour hours cycling competition in a team relay format elicited high energy demands which were not compensated by energy intake of the athletes despite that dietary consumption of macronutrients did not differ to the nutritional guidelines for longer events.